PENGEMBANGAN MODEL SIKLUS PENDAMPINGAN GURU PAI DAN TENAGA KEPENDIDIKAN PAUD NON FORMAL DI KOTA BUKITTINGGI - Rosi Afriyani; Zulfani Sesmiarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to develop a mentoring cycle model for Islamic Religious Education (PAI) teachers and education staff at non-formal PAUD institutions in Bukittinggi. This model is designed to improve pedagogical, professional and spiritual competencies through a systematic and sustainable approach. This research uses the Research and Development (R&D) method of the modified Borg & Gall model, involving needs analysis, design, development, implementation and evaluation of the mentoring cycle model for PAI teachers and education staff in Bukittinggi Non-Formal PAUD. Qualitative data was collected through interviews and observations, while quantitative data was obtained from pretest-posttest. The effectiveness of the model is measured using the N-Gain Score test. The research results show that the mentoring cycle model developed is able to provide effective guidance in improving the quality of teaching and management of education staff in non-formal PAUD Bukittinggi. Assistance is carried out through a series of activities such as training, supervision, mentoring and evaluation which are designed adaptively according to local needs. The implementation of this model also shows an increase in participant competency in the aspects of teaching skills, understanding religious material and managing institutions. Thus, this model can be a strategic solution for developing the capacity of PAI teachers and education staff in the non-formal PAUD sector in Bukittinggi.